(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2022)
The research aims to measure the gap in the level of application of the provisions of ISO 10006 2017, in the management of projects in Nineveh Governorate and the reality of the project quality management system in the Governorate of Nineveh, using the approved checklist. All levels within the reconstruction departments in Nineveh Governorate. - Weakness in adopting and applying the terms and requirements of the specification in the field investigated when implementing its projects. The study presented a set of proposals in order to reduce the gap and increase the percentage of application of the provisions of the specification (ISO 10006: 2017) in the management of regional development projects in Nineveh Governorate, including: - Motivating individuals to participate in the process of developing and implementing a quality management system, and supporting their level of awareness through Strengthening the principles of project quality management systems. - Creation of a department or division in the reconstruction department (project quality management department or division). Keywords: project management, project quality management.